A mixed-methods pilot study of 'LIFEView' audiovisual technology: Virtual travel to support well-being and quality of life in palliative and end-of-life care patients. (July 2020) - Kabir, Monisha; Rice, Jill L; Bush, Shirley H; Lawlor, Peter G; Webber, Colleen; Grassau, Pamela A; Ghaedi, Bahareh; Dhuper, Misha; Hackbusch, Rebekah
Background: There is evidence that psychosocial and spiritual interventions of short duration, such as reminiscence therapy, provide positive impacts on quality of life and emotional and existential well-being in adults receiving palliative care. Aim: To determine (1) the feasibility of integrating 'LIFEView', a video-based software with >1600 videos of world destinations, in palliative care settings, and (2) positive, neutral or harmful effects of using 'LIFEView' videos. Design: A mixed-methods pre–post intervention pilot study was conducted to collect feasibility and preliminary data on physical and psychological symptoms, physiological indicators, spiritual well-being and aspects of quality of life. Setting/participants: Adult patients on an inpatient palliative care unit or receiving care from a community palliative care consultation team who were capable of providing consent and completing the outcome measures were eligible participants. Results: Overall, 27/41 (66%) participants took part in the study. Feasibility criteria, including participant acceptability, low participant burden, tool completion rate and retention rate, were fulfilled, though challenges were experienced with recruitment. Modest improvements, though non-significant, were shown on preliminary data collected on physical and psychological symptoms using the Edmonton Symptom Assessment System–revised, spiritual well-being assessed by the 12-item Functional Assessment of Chronic Illness Therapy – Spiritual Well-Being scale and physiological measurements. Qualitative analysis revealed five themes: motivations for using 'LIFEView', perceptions of the technology, reminiscence, 'LIFEView' as an adaptable technology and ongoing or future use. Conclusion: A future adequately powered study to investigate the impacts of 'LIFEView' on patient well-being and quality of life appears to be feasible.